Pelatihan Identifikasi Kerangka Bagi Dokter Umum di Rumah Sakit PKU Muhammadiyah Gombong - Abdul Nitiprodjo; Prima Putri; Lutfatul Fitriana (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
ABSTRACT Natural and man-made disasters including criminal events result in the death of a person or all people, and can even make the human body become incomplete. This causes the SAR team to have difficulty in identifying bodies found due to the disaster. To obtain valid data regarding the identity of the bodies found, the SAR team needs to work with the body identification team. The body identification team involves police investigators, doctors and forensic anthropology experts. From these problems, doctors need to improve their competence by holding skeletal identification training for general practitioners in hospitals. The objectives and benefits of this training include: improving the knowledge and skills of general practitioners, being able to determine the right formula, especially calculating height, developing natural and man-made disaster services, especially body identification, doctors are able to work with investigators and forensic anthropology experts in establishing body identification. The stages of the method in this training activity include: compiling theories and guidelines for skeleton identification, preparing dry preparations in the form of skeletons as training materials, delivering materials, practicing identification and evaluation. The results achieved are an increase in the competence of knowledge and skills of general practitioners, especially skeleton identification. Keywords: Identification, Skeleton